1978
DOI: 10.1161/01.res.43.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Failure of chronic aldosterone infusion to increase arterial pressure in dogs with angiotensin-induced hypertension.

Abstract: SUMMARY To generate quantitative data relating to the hypertensive activity of aldosterone, 9 /xg/kg per day (4 times normal) aldosterone (4-ALDO) were infused chronically in both adrenalectomized and intact dogs until steady state conditions were achieved. Mean arterial pressure (MAP) was monitored continuously, 24 hours per day, and daily steady state values for MAP based on approximately 600 sample points per day were determined by employing computerized data analysis. In some studies, angiotensin II (A II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…The aldosterone levels in the 2 groups were similar, yet the blood pressures remained lower in the D + R -group lacking extrarenal AT 1A receptors, compared with those in D + R + controls ( Figure 6B). These findings corroborate other studies in which infusion of aldosterone alone failed to raise blood pressure (35) and suggest that the adrenal gland is not a critical site for blood pressure control by extrarenal AT 1A receptors. We speculate instead that AT 1A receptors in the CNS and/or in the vasculature are more likely to mediate the component of blood pressure regulation that is independent of the kidney.…”
Section: Figuresupporting
confidence: 90%
“…The aldosterone levels in the 2 groups were similar, yet the blood pressures remained lower in the D + R -group lacking extrarenal AT 1A receptors, compared with those in D + R + controls ( Figure 6B). These findings corroborate other studies in which infusion of aldosterone alone failed to raise blood pressure (35) and suggest that the adrenal gland is not a critical site for blood pressure control by extrarenal AT 1A receptors. We speculate instead that AT 1A receptors in the CNS and/or in the vasculature are more likely to mediate the component of blood pressure regulation that is independent of the kidney.…”
Section: Figuresupporting
confidence: 90%
“…Similarly, infusion of aldosterone at this same elevated rate in dogs with All hypertension produced marked mineralocorticoid effects but no further increase in MAP. 11 In contrast, when ACTH was infused in dogs with All hypertension, MAP increased an additional 16 mm Hg (manuscript submitted for publication). Additionally, in the present study, dogs with NE hypertension were infused with very high rates of aldosterone simul-taneously with enough cortisol to increase plasma cortisol concentration to levels comparable to those achieved with ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…11 The effects of aldosterone infusion on MAP, urinary sodium excretion, urinary potassium excretion, urine excretion, and water consumption are shown in figure 5. During the initial 10 days of aldosterone infusion, MAP increased progressively to 14 ± 3 mm Hg above control on Day 10.…”
Section: Effects Of Aldosterone Infusion In Normotensive Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,19,22 These studies indicated that no further changes in MAP, heart rate, urinary electrolyte excretion, and the plasma concentrations of aldosterone, sodium, and potassium after Ϸ5 days of Ang II infusion. That is, the 5-day values for these persisted for not less than 10 to 21 days of Ang II infusion.…”
Section: Experimental Protocolmentioning
confidence: 92%